Herbal formulations, Product Nkabinde and Gnidia sericocephala, exhibit potent in vitro activity against HIV-1 infection - Mngomezulu, Khanyisile; Madlala, Paradise; Nkabinde, Siphathimandla Authority; Nkabinde, Magugu; Ngcobo, Mlungisi; Gqaleni, Nceba (Frontiers in Pharmacology, 2025)
BackgroundWhile antiretroviral therapy (ART) has transformed HIV-1 into a manageable chronic illness, its long-term affordability and accessibility remain major challenges in resource-limited settings. Additionally, adverse side effects can compromise treatment adherence and effectiveness. These limitations highlight the need for novel, affordable therapeutic alternatives. In this study, we evaluated the anti-HIV-1 activity of Product Nkabinde (PN), a traditional herbal formulation comprising four plant extracts, and Gnidia sericocephala (G. sericocephala), to assess their potential as alternative or complementary therapies.MethodsHIV-1 subtype B and subtype C viral stocks were produced by transfecting HEK293T cells with envelope plasmids and an env-deficient HIV-1 backbone vector using polyethylenimine. TZM-bl cells were treated with PN and G. sericocephala extracts, alone or combined with antiretrovirals (AZT, raltegravir, maraviroc, amprenavir), then infected with the viruses. Viral infectivity was measured using the luciferase assay, and results were validated in peripheral blood mononuclear cells (PBMCs) using HIV-1 p24 ELISA.ResultsThe PN extract exhibited a dose-dependent antiviral effect, with the optimal concentration achieving 93% and 96% inhibition of HIV-1 subtype B and C, respectively, in TZM-bl cells, comparable to AZT. In HIV-1 infected PBMCs, treatment with AZT, PN, or G. sericocephala resulted in a sustained reduction of p24 antigen levels over 11 days compared to untreated controls. While NL4.3 showed partial inhibition (p24 levels >20,000 pg/mL), strains CM070P.1, YU2, and CM019P.1.2 exhibited consistently low p24 production levels (<20,000 pg/mL), indicating strain-dependent antiviral activity. PN, combined with maraviroc inhibited YU2 replication by 81.3% (p = 0.0361), while combinations with raltegravir and AZT suppressed subtype C strains CM070P.1 and CM019P.1.2 by 98.7% (p = 0.0083) and 99% (p = 0.0428), respectively, compared to either PN or the antiretroviral alone. Gnidia sericocephala combined with AZT inhibited NL4.3 by 80.3% (p = 0.0105), and its combinations with maraviroc, raltegravir, and amprenavir suppressed CM070P.1 replication by 87% (p = 0.0093), 86% (p = 0.0168), and 90% (p = 0.0006), respectively, relative to either test agent alone. Fractional inhibitory concentration index (FICI) analysis indicated no synergistic or antagonistic interactions.ConclusionThus, this current data suggests that PN and G. sericocephala possess anti-HIV-1 activity.